2019
DOI: 10.1017/s1049023x19004874
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Impact of Disaster on the Mental Health of Medical Responders

Abstract: Introduction:Medical responders are at-risk of experiencing a wide range of negative psychological health conditions following a disaster.Aim:Published literature was reviewed on the adverse psychological health outcomes in medical responders to various disasters and mass casualties in order to: (1) assess the psychological impact of disasters on medical responders; and (2) identify the possible risk factors associated with psychological impacts on medical responders.Methods:A literature search of PubMed, Disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

19
242
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(268 citation statements)
references
References 84 publications
19
242
0
7
Order By: Relevance
“…Depression exhibits a higher chance to raise both the risks of anxiety and burnout. Our result is in line to Nushad et al's study, which showed that health professionals in an emergency department and nurses in intensive rooms and infectious diseases ward exhibit a higher risk for adverse psychiatric effects [37]. Another study argued that 23.7% intensive care unit doctors in France experience depression [38].…”
Section: Discussionsupporting
confidence: 92%
“…Depression exhibits a higher chance to raise both the risks of anxiety and burnout. Our result is in line to Nushad et al's study, which showed that health professionals in an emergency department and nurses in intensive rooms and infectious diseases ward exhibit a higher risk for adverse psychiatric effects [37]. Another study argued that 23.7% intensive care unit doctors in France experience depression [38].…”
Section: Discussionsupporting
confidence: 92%
“…The effect of social support and coping was shown by a systematic review conducted on the impact of a disaster on the mental health of HCW. As per the report, the common risk factors for developing psychiatric morbidities were lack of social support, communication, maladaptive coping and lack of training (Naushad et al, 2019). In the current review, the effect of social support on self-efficacy, insomnia, anxiety, and depression was shown by the study done by Xiao H et al, 2020 13 .…”
Section: Discussionmentioning
confidence: 94%
“…The psychiatric illnesses that people develop include depression, anxiety, panic attacks, somatic symptoms, and posttraumatic stress disorder symptoms, to delirium, psychosis and even suicidality (Hall et al, 2008;Muller, 2014;Sim et al, 2010). As already pointed out, studies done in the past reported that HCW especially those working in emergency units, intensive care units, and infectious disease wards are at higher risk of developing adverse psychiatric impact (Naushad et al, 2019). The current review also showed similar results that HCWs are at higher risk of developing adverse psychiatric outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare workers caring for patients diagnosed with COVID 19 are at a higher risk of developing psychological distress. Taking preventive measures and providing psychological interventions tailored to these healthcare workers can positively affect this distress (Naushad et al, 2019). To date, the Chinese authorities have taken numerous decisive measures to help relieve mental stress related to the ongoing coronavirus outbreak.…”
mentioning
confidence: 99%